Using vehicle taxes to reduce carbon dioxide emissions rates of new passenger vehicles: Evidence from France, Germany, and Sweden - Thomas Klier; Joshua Linn (Federal Reserve Bank of Chicago, 2012)
France, Germany, and Sweden have recently linked vehicle taxes to the carbon dioxide (CO2) emissions rates of passenger vehicles. France has introduced a system of CO2-based purchase taxes and subsidies, whereas Germany and Sweden impose annual circulation (i.e., registration) taxes that are linear functions of CO2 emissions rates. This paper (a) compares the effects of vehicle taxes on registrations and average emissions rates across countries and (b) estimates the effect of reducing CO2 emissions rates on manufacturers' profits. The taxes have had a significant negative short-run effect on new vehicle registrations in all three countries, although the effect is somewhat stronger in France than in Germany and Sweden. We find little evidence that the French tax caused manufacturers to change the emissions rates of individual vehicles, however. The second part of the paper takes advantage of the theoretical equivalence between an emissions rate standard and a CO2-based emissions rate tax. We use the results from the first part to estimate the effect on manufacturers' profits of reducing emissions rates. Focusing on France, a decrease of 5 grams of CO2 per kilometer (about 3 percent) reduces short-run profits by 10 - 50 euros per vehicle, depending on the manufacturer. We find considerable heterogeneity across manufactures in these costs.
Keywords: L62; Q54; 330; feebate; fuel economy standards; emissions rate standards